Penerapan Triple Exponential Smoothing Model Multiplicative dan Additive untuk Memprediksi Harga Saham BRIS.JK - Noor Sofiyati (UJMC (Unisda Journal of Mathematics and Computer Science), 2025)
When investing in stocks, investors must consider not only potential returns but also the risk of loss. Like conventional stocks, sharia-compliant stocks fluctuate in value, requiring careful analysis to predict future prices. This study aims to forecast the price of sharia-compliant BRIS.JK stocks using both the multiplicative and additive triple exponential smoothing models. These methods were chosen because BRIS.JK stock data exhibits random fluctuations. The analysis uses 270 daily closing prices of BRIS.JK shares from the past five business days. The results indicate that both models predict a continuous rise in stock prices over the next 54 days (June to August 2025). The MAPE values for both models are below 10%, demonstrating excellent predictive accuracy. This insight can assist investors in deciding whether to increase their holdings of BRIS.JK shares or purchase them to maximize future profits.